Cellular automata labeling of connected components in n-dimensional binary lattices - Stamatovic, Biljana; Trobec, Roman (The Journal of supercomputing, 2016)
A new cellular automata-based algorithm for labeling of connected components in n -dimensional binary lattices, for n ≥ 2 , is proposed. The algorithm for 3D binary images was implemented in NetLogo and MatLab programming environments. The algorithm is local and can be efficiently implemented on data-flow parallel platforms with an average asymptotic complexity of O ( L ) on L n binary lattices. However, some worst-case arrangements of the n -dimensional lattice cells could require O ( L n ) calculation steps.